2002
DOI: 10.1074/jbc.m201154200
|View full text |Cite
|
Sign up to set email alerts
|

The C66W Mutation in the Deafness Dystonia Peptide 1 (DDP1) Affects the Formation of Functional DDP1·TIM13 Complexes in the Mitochondrial Intermembrane Space

Abstract: Mohr-Tranebjaerg syndrome is a progressive, neurodegenerative disorder caused by loss-of-function mutations in the DDP1/TIMM8A gene. DDP1 belongs to a family of evolutionary conserved proteins that are organized in hetero-oligomeric complexes in the mitochondrial intermembrane space. They mediate the import and insertion of hydrophobic membrane proteins into the mitochondrial inner membrane. All of them share a conserved Cys 4 metal binding site proposed to be required for the formation of zinc fingers. So far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 31 publications
6
54
0
1
Order By: Relevance
“…In human cells, deletion or loss-of-function mutations in the gene encoding 351 DDP1/TIMM8A is responsible for a rare X-linked recessive neurological disorder called 352 deafness-dystonia or Mohr-Tranebjaerg syndrome [122]. One such loss-of-function mutation 353 causes the replacement of a cysteine by a tryptophan (C66W) within the CX 3 C motif, 354 preventing the correct folding of DDP1 and consequently its ability to participate in 355 mitochondrial import reactions [123]. substrate proteins is not limited to CX n C-containing precursors but also includes proteins with 363 alternate cysteine motifs that are not organized structurally in a CHCH domain and are larger 364 in size.…”
mentioning
confidence: 99%
“…In human cells, deletion or loss-of-function mutations in the gene encoding 351 DDP1/TIMM8A is responsible for a rare X-linked recessive neurological disorder called 352 deafness-dystonia or Mohr-Tranebjaerg syndrome [122]. One such loss-of-function mutation 353 causes the replacement of a cysteine by a tryptophan (C66W) within the CX 3 C motif, 354 preventing the correct folding of DDP1 and consequently its ability to participate in 355 mitochondrial import reactions [123]. substrate proteins is not limited to CX n C-containing precursors but also includes proteins with 363 alternate cysteine motifs that are not organized structurally in a CHCH domain and are larger 364 in size.…”
mentioning
confidence: 99%
“…Nevertheless, the significance of the cysteine residues, whatever are their precise roles, is partly borne out in mutagenesis studies of homologous proteins. Mutation of the fourth cysteine residue in DDP1 (the human homologue of Tim8) affects the folding of the Tim8 protein and Tim8-Tim13 assembly (20,21). We have recently shown that the TIM10 complex is only formed between oxidized Tim 9 and Tim10 and that zinc can bind only to the fully reduced state without promoting complex formation (44).…”
mentioning
confidence: 99%
“…Bioinformatics analysis of the small Tims from a wide range of eukaryotes indicates that the Tim12 proteins are not a distinct lineage, rather having arisen independently in different organisms by duplication of one of the other four small Tims (19). Although it is nonessential in yeast, mutations in the gene encoding the human homologue of Tim8, DDP1 (deafness/ dystonia peptide 1), can cause Mohr-Tranebjaerg syndrome, an X-linked neurodegenerative disorder, characterized by deafness, dystonia, mental retardation, and blindness (20)(21)(22). The small Tim family shares a characteristic conserved twin CX 3 C motif (where X is any amino acid), the two motifs themselves being separated by 11-16 amino acids (23).…”
Section: Small Tim Proteinsmentioning
confidence: 99%